Confronting Gendered Pathways to Incarceration: Considerations for Reentry Programming - Wesely, Jennifer K. (Social justice, 2018)
Pathways both into and out of the criminal justice system are gendered, and research finds that reentry can be particularly challenging for women. Community programming has the potential to address important issues in the lives of women during this crucial time of transition, but reentry efforts pay scant attention to gendered pathways before and after incarceration. This study employs findings from interviews conducted at a women's reentry program to examine women ex-offenders' perceptions of their pathways into crime and related struggles upon reentry. Our analysis identifies three major pathways to incarceration, each with its own enduring implications for reentry: intersectional vulnerabilities, abuse and neglect, and substance abuse and compromised mental health. After examining how participants identified and described each of these three pathways, we suggest an action agenda to better address women's unique reentry needs.